Pengaruh Konsentrasi Saccharomyces cereviceae Terhadap Produksi Bioetanol Berbahan Dasar Batang Jagung - Muhammad Rijal; Abajaidun Mahulauw; Adila Rumbaru (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
This type of research is quantitative laboratory experiments. This research was conducted for 2 weeks starting from 13-25 September 2018, at the IAIN MIPA Laboratory in Ambon. The object of this research is corn stem waste found in Waiheru Village, Ambon City, Maluku Province. The results showed that there was a treatment of 1% yeast concentration producing the lowest bioethanol level of 0.26%. Whereas, 4% yeast concentration with 6 days fermentation time produced the highest bioethanol level which was equal to 1.25%. In the treatment of 1% yeast concentration produced the lowest volume of bioethanol which was equal to 92.666 ml. Meanwhile, the treatment of 4% yeast concentration produced the highest volume of bioethanol of 97,333 ml. Key Words: Saccharomyces ceriveceae, Bioethanol Production, Corn Stalks